2017
DOI: 10.1182/blood-2016-09-738070
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo drug response profiling detects recurrent sensitivity patterns in drug-resistant acute lymphoblastic leukemia

Abstract: Key Points Ex vivo drug profiling captures disease-relevant features and relevant sensitivity to therapeutic agents in ALL. A subset of drug-resistant T-ALL without mutations in ABL1 is highly responsive to dasatinib, which provides a rationale for drug repurposing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
204
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(226 citation statements)
references
References 58 publications
15
204
1
Order By: Relevance
“…In T‐ALL, primary and PDX cells were reported to be generally stable at the genomic level (Wang et al , ), although the PDX material more closely resembled the relapsed leukemias rather than the pattern observed in initial disease, which suggested that the PDX maneuver selects for subclones that may later give rise to the relapse (Clappier et al , ). Extensive genomic studies of BCP‐ALL showed that PDXs mirror the clonal composition of the original leukemia samples, including from MRD samples, with the exception of losses and gains of alternations in RAS pathway genes, which is also frequently observed in relapsed ALL (Fischer et al , ; Frismantas et al , ). Moreover, PDX models of ALL served for identification of a rare subpopulation that resembled relapse‐inducing cells whose gene expression profile was similar to primary cells isolated from patients at MRD (Ebinger et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In T‐ALL, primary and PDX cells were reported to be generally stable at the genomic level (Wang et al , ), although the PDX material more closely resembled the relapsed leukemias rather than the pattern observed in initial disease, which suggested that the PDX maneuver selects for subclones that may later give rise to the relapse (Clappier et al , ). Extensive genomic studies of BCP‐ALL showed that PDXs mirror the clonal composition of the original leukemia samples, including from MRD samples, with the exception of losses and gains of alternations in RAS pathway genes, which is also frequently observed in relapsed ALL (Fischer et al , ; Frismantas et al , ). Moreover, PDX models of ALL served for identification of a rare subpopulation that resembled relapse‐inducing cells whose gene expression profile was similar to primary cells isolated from patients at MRD (Ebinger et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting Information Figure S4A‐D shows the dose‐response curves of all four PDXs with IC 50 values summarized in Supporting Information Figure S4E. The IC 50 observed for ALL‐93 was much higher in coculture (3.9 µM) compared with monoculture (58.7 nM), consistent with previous reports where MSCs provided survival signals and contributed to chemoresistance . However, no notable differences were observed between coculture and monoculture conditions in the other three PDXs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work indicates that resistant/relapsed ALL cells are particularly vulnerable to SMAC mimetics and cell death is orchestrated through routes distinct from conventional chemotherapeutic agents [55]. Finally, ex vivo profiling of resistant B ALL samples showed that a subset of B ALL samples were quite sensitive to Bcl-2 selective BH3 mimetic inhibitor venetoclax [56]. This has been validated in xenograft models particularly MLL rearranged leukemias although other BH3 mimetics may have broader activity [57].…”
Section: Targeting Underlying Mechanisms Of Relapsementioning
confidence: 99%